MODEL PERUBAHAN SERAPAN MINYAK PADA KENTANG SELAMA PENGGORENGAN - Rina Pratiwi Pudja, Ida Ayu (Universitas Udayana, 2007)
Frying is one of fast and practical of cooking process of food using fat or oil media. The aims of the research were to find out, test and apply the model of oil absorption in potatoes during frying . Frying temperatures was adjusted at 1400C, 1600C and 1800C, with interval time to analysis at 0, 30, 90, 150, 300, dan 600 second. Fresh potatoes were cut in cylinder shaped with diameter of 0,9 cm and 4 cm long. The result showed that the higher frying temperature, the higher absorption of fat during frying. The rate of fat absorption could be analogically expressed as the Newton model for cooling, to prediction absorption of fat during frying in fresh potatoes in other temperature.